Prototyping Adaptive Cruise Control on Electric Motorcycle. Issue 1 (March 2021) - Purba, D A; Nizam, M; Maghfiroh, H; Putra, M R A; Inayati
Abstract: Electric motorcycle is one of the vehicles that can operate using alternative fuels, namely with electrical energy. Travel between cities over great distances, of course this results in a high risk of accidents. Additional features are needed that can warn and stop the electric motorcycle before crashing into other vehicles in front of it. Cruise Control is an automatic technology that is embedded in the automotive system to maintain a constant speed. Prototype refers to the physical and digital representation of pre-production models. This research focuses on applying ultrasonic sensors as distance detectors for the prototype adaptive cruise control system which will be installed as an additional feature on electric motorcycles. The method used in this research starts from simulating a series of systems on Proteus 7.9 software, then designing electrical and software devices on prototyping, and testing. The results obtained by adaptive cruise control mode by testing the variation of distance to PWM duty cycle changes in the simulation compared to prototyping, found an error of ± 1.53%, this shows the prototype Adaptive Cruise Control can work well.